2009
DOI: 10.1289/ehp.0800522
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Phthalate Metabolites in Relation to Preterm Birth in Mexico City

Abstract: BackgroundRates of preterm birth have been rising over the past several decades. Factors contributing to this trend remain largely unclear, and exposure to environmental contaminants may play a role.ObjectiveWe investigated the relationship between phthalate exposure and preterm birth.MethodsWithin a large Mexican birth cohort study, we compared third-trimester urinary phthalate metabolite concentrations in 30 women who delivered preterm (< 37 weeks of gestation) with those of 30 controls (≥ 37 weeks of gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
161
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 232 publications
(174 citation statements)
references
References 49 publications
10
161
2
1
Order By: Relevance
“…The total daily intake of DEHP was 108.5 μg/day and DEP -176.5 μg/day; which is close to the values calculated based on the same model by Koch et al (2003) [46]. It needs to be pointed that in majority of the studies in this field, the assessment of exposure was based on phthalate levels in urine collected, as in our study, during the third trimester of pregnancy [11,13,16,17] or in cord blood [4][5][6]. Additionally, the recently published study by in which phthalate metabolites were measured 4 times in pregnancy period, has indicated that urinary phthalate metabolite levels showed moderate individual and population-wide variability during pregnancy, and that most of them demonstrated a slightly downward sloping trend across gestation [14].…”
Section: Confounding Factorssupporting
confidence: 86%
See 3 more Smart Citations
“…The total daily intake of DEHP was 108.5 μg/day and DEP -176.5 μg/day; which is close to the values calculated based on the same model by Koch et al (2003) [46]. It needs to be pointed that in majority of the studies in this field, the assessment of exposure was based on phthalate levels in urine collected, as in our study, during the third trimester of pregnancy [11,13,16,17] or in cord blood [4][5][6]. Additionally, the recently published study by in which phthalate metabolites were measured 4 times in pregnancy period, has indicated that urinary phthalate metabolite levels showed moderate individual and population-wide variability during pregnancy, and that most of them demonstrated a slightly downward sloping trend across gestation [14].…”
Section: Confounding Factorssupporting
confidence: 86%
“…Results of the studies of the impact of phthalates on pregnancy duration are not consistent. In the studies that measured phthalate metabolite levels in cord blood or, similarly as in our study, in the urine collected in the third trimester of pregnancy, 4 noted significant associations with shortened pregnancy duration or increased odds of preterm birth [4,6,16,17], while 2 other studies indicated longer gestation with an increase in concentrations of phthalate metabolites (which as suggested by Wolff et al (2009) can result from residual confounding) [11,13]. No association was noted by Suzuki et al (2010) [10].…”
Section: Phthalate Exposure and Pregnancy Duration And Birth Outcomessupporting
confidence: 77%
See 2 more Smart Citations
“…Furthermore, there appear to be relationships of environmental toxins with birth at lower gestational age, and phthalates [55,56] and perfluorinated compounds [51,53] with preterm birth.…”
Section: -29 ≥30mentioning
confidence: 99%